Effectiveness of music therapy and Tai Chi exercise on anxiety, depression and quality of life for patients with cancer: a protocol for systematic reviews and meta-analysis - Zhang, Le; Zhang, Zixue; Wang, Feng (BMJ Publishing Group, 2025)
Introduction Patients with cancer frequently suffer from psychological distress, including anxiety and depression, which negatively impacts their quality of life. Music therapy (MT)and Tai Chi exercise are emerging as promising complementary interventions in cancer care. However, their comparative effectiveness remains uncertain. This systematic review aims to evaluate and compare the effects of MT and Tai Chi exercise on anxiety, depression and quality of life among patients with cancer. Methods and analysis Following the Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P) guidelines, a comprehensive search will be conducted in databases including PubMed, Web of Science, Scopus and CNKI for randomised controlled trials (RCTs) published up to March 2025. Studies assessing the effects of either intervention on cancer patients will be included. The primary outcomes are anxiety and depression, while quality of life is considered a secondary outcome. All outcomes will be measured using validated instruments. Two reviewers will independently screen, extract data and assess study quality using the Cochrane Risk of Bias tool. Meta-analyses will be performed using RevMan where appropriate, along with analyses of heterogeneity, publication bias and sensitivity. Ethics and dissemination Ethical approval is not required as the study involves secondary data analysis. Results will be disseminated through peer-reviewed journals and conferences. This review will offer evidence-based insights to guide cancer rehabilitation strategies involving mind-body and music-based therapies.